Metaontology for description of decision-making process - Мелешко, М. А.; Чаплінський, Ю. П. (Problems of Informatization and Control, 2015)
Actuality of the study of 3D-technology is shown. Areas of educational resource for the study of 3D-technology were identified and described. The levels of detail of 3D-objects were presented and discussed. The semantic representation of the 3D multimedia elements and multimedia projects were considered